2021
DOI: 10.1111/vru.12959
|View full text |Cite
|
Sign up to set email alerts
|

The use of fluorine‐18‐fluorodeoxyglucose‐positron emission tomography/computed tomography as an effective method for staging in dogs with primary appendicular osteosarcoma

Abstract: Fluorine-18-fluorodeoxyglucose ( 18 F-FDG) positron emission tomography/computed tomography (PET/CT) has been utilized in veterinary medicine to improve the detection and characterization of primary, recurrent, and secondary neoplasms; but its use as a staging tool for dogs diagnosed with appendicular osteosarcoma has not been published. The purpose of this retrospective, case series, descriptive study was to detail the use of 18 F-FDG PET/CT for staging a population of dogs with appendicular osteosarcoma, rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 30 publications
(123 reference statements)
0
17
0
Order By: Relevance
“…1,2 Due to the high metastatic rate seen with osteosarcoma, appropriate staging of patients prior to treatment is imperative to help determine prognosis and best therapeutic recommendations. [2][3][4] Treatment is often based on a multimodal approach, incorporating surgery, chemotherapy and/or radiation therapy. 5 Traditionally, modalities for staging canine patients with appendicular osteosarcoma have included thoracic radiographs and/or thoracic computed tomography (CT) for assessing for pulmonary metastasis and nuclear scintigraphy for detecting osseous lesions.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…1,2 Due to the high metastatic rate seen with osteosarcoma, appropriate staging of patients prior to treatment is imperative to help determine prognosis and best therapeutic recommendations. [2][3][4] Treatment is often based on a multimodal approach, incorporating surgery, chemotherapy and/or radiation therapy. 5 Traditionally, modalities for staging canine patients with appendicular osteosarcoma have included thoracic radiographs and/or thoracic computed tomography (CT) for assessing for pulmonary metastasis and nuclear scintigraphy for detecting osseous lesions.…”
mentioning
confidence: 99%
“…Fluorine-18-fluorodeoxyglucose positron emission tomography/computed tomography ( 18 F-FDG PET/CT) has recently been incorporated into staging protocols at our institution. 4 In human paediatric studies, 18 F-FDG PET/CT has been found to have higher sensitivity, specificity and diagnostic accuracy compared to bone scintigraphy in identifying distant bone metastases in patients with osteosarcoma. 6 The utility of 18 F-FDG PET/CT for staging canine patients with appendicular OSA has only recently been reported, 4 however a direct comparison to other imaging modalities…”
mentioning
confidence: 99%
See 3 more Smart Citations